2013
DOI: 10.14419/ijbr.v1i2.1368
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Inclusion of Column Feeder Rohu (Labeo Rohita) at Different Stocking Densities on Growth and Production in Freshwater Prawn-Finfish Polyculture System

Abstract: The research investigated the impacts of inclusion of column feeder rohu (Labeo rohita) on growth and production in freshwater prawn-carp-mola polyculture system for a period of 172 days. Four stocking densities of Rohu were maintained as 500, 1,000, 1,500 and 2,000 ha -1 in treatment R 500 , R 1000 , R 1500 and R 2000 , respectively in triplicates. All ponds each 120 m 2 were stocked with juvenile freshwater prawn (Macrobrachium rosenbergii), silver carp (Hypophthalmichthys molitrix), catla (Catla catla) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…Overall, NO 2 -N and TAN concentrations increased and DO decreased over time (Figure 1). Treatment × time interaction was significant on all measured water-quality parameters except pH (Ahsan et al 2013;Siddik et al 2014). Dissolved oxygen, pH, nitrite-N, and TAN varied over the experimental period between 5.2-6 mg l −1 , 7.6-8.2 mg l −1 , 0.02-2.5 mg l −1, and 0.01-1.2 mg l −1 , respectively.…”
Section: Resultsmentioning
confidence: 90%
“…Overall, NO 2 -N and TAN concentrations increased and DO decreased over time (Figure 1). Treatment × time interaction was significant on all measured water-quality parameters except pH (Ahsan et al 2013;Siddik et al 2014). Dissolved oxygen, pH, nitrite-N, and TAN varied over the experimental period between 5.2-6 mg l −1 , 7.6-8.2 mg l −1 , 0.02-2.5 mg l −1, and 0.01-1.2 mg l −1 , respectively.…”
Section: Resultsmentioning
confidence: 90%
“…Water quality parameters Daily water temperature, dissolved oxygen, and pH over three experiments fluctuated in the ranges of 26.5-30.2°C, 4.90-5.66 mg/L, and 7.1-8.3, respectively. These factors were generally within the suitable range for tropical fish growth (Boyd 2003;Siddik et al 2014b;Ahsan et al 2013). However, the mean concentrations of dissolved inorganic nitrogen such as NO2 and TAN ranged from 0.04 to 1.85 mg/L and 0.02-0.97 mg/L, respectively.…”
Section: Resultsmentioning
confidence: 92%
“…Margalef in the study area was ranged from 4.6 to 8.471 which indicated the river had healthy to high-quality food chains. In general, diversity indices value varied depending upon the number of species as well as a number of individuals in each fish species [11,32,41].…”
Section: Fish Diversity Indicesmentioning
confidence: 99%
“…Thus, the river has great influence to change life pattern and sustain of riverine population community the southern coastal region of Bangladesh primarily depend on resources from the river. But at the meantime, the worthwhile aquatic resources of Sandha River are in declining trends like others water resources of Bangladesh due to both anthropogenic activities and environmental alterations [4,10,11]. Very earlier study by Hanif et al [12] identified total 26 threatened fish species from Sandha River and found environmental degradation and over-exploitation using restricted fishing gears was the important factors for threatening the ichthyofaunal community.…”
Section: Introductionmentioning
confidence: 99%